(untitled) - Hane, Mikiso (New York, 1972)
In this newly revised edition of his readable and thoughtful survey, Mikiso Hane presents the essential facts of modern Japanese history. He integrates political events with the cultural, economic, and intellectual activities of each period, and he is sensitive to the conditions of life in all strata of the population...